EFL Learners’ Responses on the Use of Performance-based Assessment - Entika Fani Prastikawati (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2018)
Assessment is an ongoing process of evaluating learners’ ability or skill after process of teaching and learning. In English class, assessment also plays an important role. According to the facts found, assessment mostly used in English class is traditional assessment. English class needs more alternative assessments to set the goals of learning English. Curriculum 2013, which is used in Indonesia right now, emphasizes the use of authentic assessment, and performance – based assessment is to be a subset of authentic assessment. This article is trying to discuss the students’ responsess on the use of performance-based assessment applied by the English teachers. This study applied descriptive qualitative research design. The subjects of this research were 30 Senior High School students. To collect the data needed, this study used observation and interview as the instrument. The observation was used to discover performance-based assessments which had already been applied by the English teachers in school. The result of the interview was interpreted to clarify the students’ responsess on the use of performance-based assessment applied by the English teachers. Performance-based assessments which had already been applied were role-plays, writing sample, and retelling. From 6 classes, 3 classes (50%) applied role-plays. Moreover, 2 (33,3%) classes applied writing sample, and the rest applied retelling (16,66%). It means that role-plays was performance-based assessment which was mostly applied by the English teachers. Furthermore, the students’ responsess on the use of performance-based assessment was good. Almost of the 30 students considered that performance-based assessment can improve their English skills and confidence instead of traditional assessment. 24 of the 30 students also claimed that traditional assessment is still inadequate to activate their English skill. In short, 80% of 30 students gave a positive responsess on the use of performance-based assessment.